Loss-of-Function in SMAD4 Might Not Be Critical for Human Natural Killer Cell Responsiveness to TGF-β - Lachlan P. Healy; Lachlan P. Healy; Gustavo R. Rossi; Gustavo R. Rossi; Jai Rautela; Charlotte A. Slade; Charlotte A. Slade; Charlotte A. Slade; Nicholas D. Huntington; Nicholas D. Huntington; Ingrid M. Winship; Ingrid M. Winship; et al. (Frontiers in Immunology, 2019)
We characterized the NK cell phenotype and function in three family members with Hereditary Hemorrhagic Telangiectasia (HHT) due to heterozygous SMAD4 mutations. Loss-of-function mutation in this gene did not induce developmental effects to alter CD56bright or CD56dim NK cell subset proportions in peripheral blood; and did not result in major differences in either their IL-15-induced proliferation, or their cytokine secretion response to TGF-β1. These data suggest that SMAD4 plays a redundant role in downstream TGF-β signaling in NK cells.